Exploring the hidden synergy between system thinking and patient safety competencies among critical care nurses: a cross-sectional study - Amal Diab Ghanem Atalla; Rwan Ragab Rabea Bahr; Ahmed Abdelwahab Ibrahim El-Sayed (BMC Nursing)
Abstract Background Patient safety remains a global priority, with nurses playing a crucial role in minimizing errors and improving patient outcomes. System thinking, which involves understanding how various components of a healthcare system interact, is increasingly recognized as essential for enhancing patient safety competencies. Aim This study investigates the impact of systems thinking on patient safety competencies among nurses in critical care units, exploring the relationship between systems thinking and various subdomains of patient safety competencies. Methods A cross-sectional study was conducted at all critical care units of Alexandria Main University Hospital, Egypt. Data were collected from a convenience sample of 289 nurses using the system thinking scale and the patient safety competency self-evaluation questionnaire. Correlation and regression analyses were performed to examine the relationship between systems thinking and patient safety competencies, controlling for demographic factors such as age, qualifications, and years of experience. Results Nurses demonstrated moderate to high levels of systems thinking (mean = 82.36 ± 12.14) and patient safety competencies (mean = 162.74 ± 23.56). Strong positive correlations were found between systems thinking and patient safety competencies (r = 0.605, p < 0.05), particularly in areas such as error reporting, communication, and infection prevention. Regression analysis revealed that systems thinking significantly predicted patient safety competencies, increasing the explained variance from 58.8 to 67.7%. Conclusion The findings highlight the critical role of systems thinking in enhancing nurses’ patient safety competencies. Nurses with higher systems thinking skills are better equipped to prevent errors and improve communication, ultimately enhancing patient care quality. Implications Nursing schools should integrate system thinking into nursing curricula to prepare future nurses for complex healthcare environments. Healthcare organizations should incorporate system thinking into professional development programs to enhance the competencies of practicing nurses. Nurse managers can foster a culture of safety by promoting interdisciplinary collaboration and reflective practice. Broader adoption of system thinking can improve patient outcomes, especially in resource-constrained environments. Clinical trial number Not applicable.